Prognostication of Half-Life Clearance of Plasma EBV DNA in Previously Untreated Non-metastatic Nasopharyngeal Carcinoma Treated With Radical Intensity-Modulated Radiation Therapy - Chan, Sik-Kwan; Chan, Sum-Yin; Choi, Horace Cheuk-Wai; Tong, Chi-Chung; Lam, Ka-On; Kwong, Dora Lai-Wan; Vardhanabhuti, Varut; Leung, To-Wai; Luk, Mai-Yee; Lee, Anne Wing-Mui; Lee, Victor Ho-Fun (Frontiers in Oncology, 2020)
Introduction: The prognostic role of plasma EBV DNA clearance when intensity-modulated radiotherapy (IMRT) and the 8th edition of AJCC/UICC TNM Staging Classification are fully implemented remains undeciphered. We investigated if its half-life clearance during radical treatment for non-metastatic NPC was an early prognosticator. Patients and Methods: Patients with previously untreated non-metastatic NPC were prospectively treated with radical IMRT and concurrent chemotherapy +/- induction/adjuvant chemotherapy from 2014 to 2018. Their plasma EBV DNA was measured immediately before treatment followed by weekly schedules until 0 copy/ml in two consecutive measurements. Cox regression models were employed to identify prognostic factors. Results: Forty-five patients were prospectively recruited and analyzed. After a median follow-up of 30.3 months, 2 (4.5%), 1 (2.3%) and 6 (13.6%) patients experienced local, regional and distant relapses respectively. The median half-life clearance of plasma EBV DNA was 7.92 days. Those with half-life clearance of >15 days had a worse 3-year progression-free survival (PFS) (79.5% vs. 25.0%, p = 0.005), distant metastasis-free survival (DMFS) (85.0% vs. 31.3%, p = 0.009) and overall survival (OS) (91.3% vs 75.0%, p = 0.024) when compared to those with a shorter half-life. Multivariable analyses demonstrated that only half-life (>15 days) was prognostic of DMFS (HR [95% CI]: 4.91 [1.31; 18.39], p = 0.01) and OS (HR [95% CI]: 5.24 [1.06; 26.05] while half-life (>15 days) (HR [95% CI]: 5.14 [1.28; 22.73], p = 0.02) and sum of pre-treatment gross tumor volumes of the primary nasopharyngeal tumor and the radiologically positive neck nodes (GTV_P+N) (HR [95% CI]: 1.01 [1.00; 1.03], p = 0.02) were prognostic of PFS. Conclusion: The half-life clearance of plasma EBV DNA was prognostic in non-metastatic NPC staged and treated in the contemporary era. Earlier biomarker surveillance during treatment should be considered.